Ta'tsīru Sukrāmbal (Scramble) 'alā tarqiyati al-mufradāti ladā thālibāti ash-shaffi ats-tsāmini bi madrasati Nūri al-Azhari al-mutawassithati al-islāmiyyati Sūkādānā Lūmbūk ash-Syarqiyyah. - Nurshofiyya Hidayati; Abdul Azis (Pascasarjana Universitas Islam Negeri Mataram, 2026)
Mastery of Arabic vocabulary is one of the fundamental aspects of Arabic language learning, as vocabulary serves as the foundation for listening, speaking, reading, and writing skills. However, the reality of classroom learning shows that some female students feel bored and demonstrate low participation due to the use of conventional teaching methods. Based on Johnson & Johnson’s Cooperative Learning Theory, which emphasizes individuals’ ability to communicate with peers, exchange ideas and perspectives, share information, understand others’ ideas, and work together to achieve common goals, there is a need for a learning model that actively and collaboratively engages students. One learning model that aligns with this theory is the Scramble learning model, as it encourages cooperation, active participation, and interaction among students in arranging and understanding vocabulary. This study aims to determine the effect of using the Scramble learning model on improving Arabic vocabulary among female students. The study employed a quantitative approach with an pre-experimental research design using the One Group Pretest–Posttest Design. The research sample consisted of all eighth-grade female students at SMP Islam Nurul Azhar Sukadana East Lombok, selected through the Convenience Sampling technique. The research instrument was an Arabic vocabulary test. Data were analyzed using the One Sample t-Test by comparing the mean posttest scores with the minimum mastery standard. The results showed that: a) the mean Arabic vocabulary score of the students after the implementation of the Scramble learning model increased from an average score of 48 to 73 and b) based on the results of the One Sample t-Test, the significance value (Sig.) of 0.000 < 0.05 indicates that the use of the Scramble learning model has a statistically significant effect on improving Arabic vocabulary among female students. Therefore, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected.